Static and Dynamic Comparison of Monetary and Non-monetary Multidimensional Poverty: Evidence from Morocco (The Pakistan Development Review, 2024)
This paper compares monetary and non-monetary poverty in Morocco from 2013 to 2019 using Enquete Panel des Ménages (EPM) data. It finds that while the incidence of poverty has fallen substantially during this period, there exists an important mismatch between both measures that is not resolved when taking a dynamic lens. On a static level, while displaying similar headcounts, the two measures identified different populations as poor and had different poverty determinants. Taking a dynamic lens, we find that the level of mismatch between the two measures does not improve: Despite similar levels of mobility, transitions in poverty status in one measure are not accompanied by simultaneous transitions in the other measure. We thus suggest the concomitant use of both monetary and multidimensional measures when targeting the poor.